An unusual focus of extra pulmonary tuberculosis - Sharma, Nilima; Sharma, Anuj; Pujani, Mukta; Kohli, Sunil (International Journal of Advances in Medicine, 2017)
Extrapulmonary tuberculosis (EPTB) is an uncommon form of chronic infection, which does not present with the typical signs and symptoms of pulmonary tuberculosis. Most extrapulmonary forms of tuberculosis affect organs with suboptimal conditions for bacillary growth. Therefore, extrapulmonary tuberculosis generally has an insidious presentation, a slow evolution, and paucibacillary lesions and/or fluids. Access to the lesions through secretions and body fluids is not always possible; therefore, invasive techniques may be necessary to obtain material for diagnostic investigation. Oral tuberculosis lesions are infrequent and their occurrence is usually secondary to pulmonary involvement. Here is an unusual presentation of oral TB which was unraveled incidentally during a routine dental extraction.